Review of developments in porous membranes and net-type structures for breakwaters and fish cages. (15th March 2020) - Guo, Y.C.; Mohapatra, S.C.; Guedes Soares, C.
Abstract: A literature review is presented on the theoretical, numerical, and experimental progress made in the application of porous membranes and net-type structures to breakwaters and fish cages. Initially, a brief discussion on modelling approaches of the porous membranes and net-type structures associated with theoretical and numerical analysis are discussed based on the frequency domain and time domain. Further, the basic mathematical equations associated with different analytical and numerical models of flexible porous membranes and net-type structures are presented. Next, various types of physical models of the sea cages and net-type floating breakwaters for the dynamic analysis of sea cages and net-type structures with action of waves and uniform currents are surveyed in detail. Further, the comparisons of numerical and experimental of different fish cage models associated with net-type structures are presented and results are discussed. Finally, conclusions of the present revision and useful recommendations in relation to future research developments and directions within the field of porous membranes and net-type structures are discussed. Highlights: A review is presented on the progress in the application of porous membranes and net-type structure to floating breakwaters The basic equations of analytical and numerical models of flexible porous membrane and net-type structures are discussed. various types of models for the dynamics of porous membrane and net-type structures are discussed.